NUZŪL AL-QUR’ĀN: GRADUALIZATION PROCESS AND LIVING GUIDELINES FOR INDONESIAN SOCIETY - Khairunnisa, Resa; Harahap, Nur Samsia; Adawiyah, Siti Wida (Universitas Nurul Jadid, 2023)
The discussion of this article is related to the nuzulul Qur'an. The Qur'an was revealed to answer all existing problems. So every verse that is revealed, must be understood by humans as the context, problems, challenges, and phenomena they are facing. The Quran is the word of God that has been delivered to the Prophet Muhammad for his people. The purpose of this research is to find out the process of gradualization of the Qur'an and the Qur'an is a guide to life for them. This research method uses a qualitative method, using library research, namely by examining materials from theories related to the problems discussed based on books related to the nuzul of the Qur'an that can support or support the author's research, and with primary data sources are selected verses of the Qur'an related to the nuzul of the Qur'an. The researcher found that the nuzul of the Qur'an is very meaningful for the life of the people. The author concludes that the Qur'an itself was revealed to all people for their salvation in this world and in the hereafter. And the lowering of the Qur'an there are many wisdoms given by Allah ta'ala as a guide to the lives of people on this earth, especially for the people of Indonesia